Uncertainty quantification in section-balancing using Pseudo-3D forward modeling – Example of the Malargüe Anticline, Argentina. (December 2020) - Witte, J.; Oncken, O.
Abstract: Quantifying uncertainty in balancing cross-sections is an insufficiently resolved challenge. We present a new workflow to assess uncertainty of selected modeling parameters. In contrast to conventional restoration, we focus on forward modeling and mapping uncertainty in solution space. We test the approach by applying trishear as the most appropriate mechanism reproducing associated fault-fold systems. We present a new structural model of the exceptionally well exposed, thick-skinned Malargüe Anticline, located in the Malargüe Foldbelt, Neuquén Basin, Argentina. Several structural models of varying quality have been published by oil explorers and researchers, but lack detailed kinematic assessment. To minimize uncertainty, we systematically vary the key modeling parameters "shortening" and "ramp angle" to reduce the cross-sectional area difference, the misfit, between model and observation. We find that the misfit is highly sensitive to these two parameters. The total uncertainty for a single structure w.r.t. these values rarely undercuts 7%. Apparently dependencies exist between these parameters. We recommend this method be extended to other parameter combinations and tectonic settings. Our analysis results in new shortening rates for the MA (up to 1.57 mm/yr) and a refined genetic model, whereby the anticline was generated during Andean contraction, rather than evolving from a pre-existing structure. Highlights: Uncertainty quantification in cross-section balancing remains a challenge. Forward modeling in parameter space is developed for misfit mapping. The cross-sectional misfit is sensitive to selected key parameters. Misfit mapping reveals dependencies between modeling parameters. The Malargüe Anticline likely formed as a new structure during Andean contraction.